INTERACTIONS WITH MUSCLE CELLS BOOST FUSION, STEMNESS AND DRUG RESISTANCE OF PROSTATE CANCER CELLS - Uygur, Berna (Mol Cancer Res, 2018)
Poorly understood interactions with non-malignant cells within the tumor microenvironment play an important role in cancer progression. Here, we explored interactions between prostate cancer and muscle cells that surround the prostate. We found that co-culturing of prostate cancer cells with skeletal or smooth muscle cells expands the subpopulations of cancer cells with features characteristic of cancer stem-like cells, including anchorage-independent growth, elevated CD133 expression and drug resistance. These changes in the properties of cancer cells depended on: (1) the muscle cell-induced increases in the concentrations of interleukins 4 and 13; (2) the cytokine-induced upregulation of the expression of syncytin 1 and annexin A5; and (3) cancer cell fusion. In human prostate cancer tissues, expression of syncytin 1 and annexin A5, proteins that we found to be required for the cell fusion, positively correlated with the cancer development suggesting that these proteins can be used as biomarkers to evaluate cancer progression and potential therapeutic targets.